The Influence of Instagram Social Media Marketing and E-WOM on Beach Visit Decisions - Deanna Loren Siregar; Aida Sari; Faila Shofa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
One of the key instruments for advertising travel destinations is the growth of social media, particularly Instagram. Nevertheless, a large number of Instagram followers does not automatically translate into a large number of visitor visits. Rio By The Beach Beach in Kalianda, South Lampung had the most visitors during the 2025 holiday season, despite having fewer Instagram followers than other beach attractions. This condition suggests that the effectiveness of electronic word-of-mouth (E-WOM) and social media marketing may have a significant impact on travelers' decisions to visit. Thus, the purpose of this study is to ascertain how tourists' decisions to visit Rio By The Beach in Kalianda, South Lampung, are influenced by Instagram social media marketing and electronic word-of-mouth. This study examines 170 visitors to Rio By The Beach using a quantitative methodology and selective sampling strategies. Questionnaires were sent as part of the data collection process, and SPSS software was utilized for multiple linear regression data analysis. The study's findings show that electronic word-of-mouth and Instagram social media marketing significantly and favorably influence travelers' decisions to visit. Electronic word-of-mouth has a greater impact than the other one. The study's conclusions suggest that tourism destination managers should concentrate their marketing efforts more on user interaction, high-quality information, and developing travel experiences that can promote the creation of positive electronic word-of-mouth (E-WOM) in order to boost travelers' decisions to come.